Structure and collective dynamics of liquid sodium - Patel, V.N.; Thakor, P.B.; Thakore, B.Y.; Gajjar, P.N.; Jani, A.R. (Condensed Matter Physics, 2006)
The temperature variation of the longitudinal and transverse phonon frequencies of liquid sodium is investigated
using the approach by Hubbard Beeby. The molecular dynamics simulation is used to generate the pair
correlation function of liquid sodium at various temperatures viz. T = 378 K, 473 K, 573 K, and 723 K, with
672 particles. To describe the electron-ion interaction our own model potential is employed along with a recent
local field correction function due to Sarkar et al. To evaluate the parameter of the potential the zero pressure
condition has been applied. The present results of g(r) are in good agreement with available experimental
findings. The computed g(r) are used to investigate the temperature variation of the collective dynamics of
liquid sodium. The amplitudes of the peaks of the longitudinal and transverse frequencies are suppressed
while the width of the propagation gap for the transverse sound waves decreases with an increase in temperature.
The computed longitudinal and transverse sound velocities at these temperatures are found to be
encouraging. За допомогою методу Габбарда-Бiбi дослiджувалась температурна залежнiсть повздовжньої та поперечної фононних частот рiдкого натрiю. Парна кореляцiйна функцiя рiдкого натрiю була запропонована при рiзних температурах, а саме T = 378 K, 473 K, 573 K та 723 K, застосовуючи метод
молекулярної динамiки для 672 частинок. Опис електрон-iонної взаємодiї здiйснювався за допомогою запропонованого авторами модельного потенцiалу, доповненого функцiєю Серкара та iн., що
описує поправку на локальне поле. Щоб оцiнити параметр потенцiалу, була застосована умова нульового тиску. Отриманi результати для g(r) добре узгоджуються з експериментальними даними.
На основi обчисленої g(r) вивчалась температурна залежнiсть колективної динамiки рiдкого натрiю.
Показано, що з пiдвищенням температури амплiтуди максимумiв повздовжньої i поперечної частот
понижуються, а ширина пропагаторної щiлини для поперечних акустичних хвиль звужується.